Recombinant fusion protein expression of Indonesian isolate Newcastle disease virus in Escherichia coli BL21(DE3) - Martha Purnami Wulanjati; Lucia Dhiantika Witasari; Nastiti Wijayanti; Aris Haryanto (Society for Indonesian Biodiversity, 2021)
Abstract. Wulanjati MP, Witasari LD, Wijayanti N, Haryanto A. 2021. Recombinant fusion protein expression of Indonesian isolate Newcastle disease virus in Escherichia coli BL21(DE3). Biodiversitas 22: 3249-3255. Newcastle disease is a major problem in poultry industry due to high mortality of susceptible chicken. New vaccine agents are important to be developed to eliminate the disease threat. This study aimed to examine the expression of fusion (F) protein of Newcastle Disease Virus (NDV) from Indonesian isolates in E. coli BL21(DE3) by IPTG induction. The sample was a part of F gene of NDV from Galur, Kulon Progo, Yogyakarta, Indonesia (0663/04/2013) with a molecular size of 600 bp that was synthesized and inserted into pBT7-N-His expression vector. The recombinant F protein with molecular weight of 25.6 kDa was successfully expressed in E. coli BL21(DE3), purified using Ni-NTA magnetic silica beads, and confirmed by western blotting. Optimization of expression showed that recombinant F protein was optimally expressed by induction of 1.0 mM IPTG when the cells reached OD600 = 0.6. The induction duration was 8 h. B-cell epitopes prediction showed that F protein possessed four epitopes that possibly recognized by B-cell. Since recombinant F protein was considered to possess immunogenicity, its potency as a candidate of NDV vaccine agent should be investigated in the future.